2016
DOI: 10.1002/jsfa.7621
|View full text |Cite
|
Sign up to set email alerts
|

Biodegradable poly-3-hydroxybutyrate as a fertiliser carrier

Abstract: The slow-release nitrogen formulations developed in this study can be buried in soil together with seeds preventing nitrogen deficiency. The use of such slow-release formulations can decrease the amounts of chemicals in the environment and prevent their adverse effects on the biosphere. © 2016 Society of Chemical Industry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 21 publications
0
29
0
Order By: Relevance
“…The present study builds on our previous work, 13 where DCD was extruded as a composite material within a biodegradable polymer matrix, namely poly(3‐hydroxybutyrate‐ co ‐3‐hydroxyvalerate) (PHBV). This bacterial polyester has been studied extensively for the controlled release of drugs, 14–16 food packaging additives 17 and agrichemicals 18–22 due to its ability to slow the rate of water diffusion, biocompatibility and biodegradability in almost any environment, including soils, fresh water systems and oceans. Our previous study revealed that, at loading of 250 g kg −1 mobilization of DCD from the PHBV matrix occurs via four distinct mechanisms: (i) initial rapid dissolution of surface available DCD, (ii) channelling of water through voids and pores in the PHBV matrix, (iii) gradual diffusion of water and DCD through layers of PHBV, and (iv) biodegradation of the PHBV matrix 13 .…”
Section: Introductionmentioning
confidence: 99%
“…The present study builds on our previous work, 13 where DCD was extruded as a composite material within a biodegradable polymer matrix, namely poly(3‐hydroxybutyrate‐ co ‐3‐hydroxyvalerate) (PHBV). This bacterial polyester has been studied extensively for the controlled release of drugs, 14–16 food packaging additives 17 and agrichemicals 18–22 due to its ability to slow the rate of water diffusion, biocompatibility and biodegradability in almost any environment, including soils, fresh water systems and oceans. Our previous study revealed that, at loading of 250 g kg −1 mobilization of DCD from the PHBV matrix occurs via four distinct mechanisms: (i) initial rapid dissolution of surface available DCD, (ii) channelling of water through voids and pores in the PHBV matrix, (iii) gradual diffusion of water and DCD through layers of PHBV, and (iv) biodegradation of the PHBV matrix 13 .…”
Section: Introductionmentioning
confidence: 99%
“…PHAs are synthesized by prokaryotes as energy and carbon storage; they are degraded both intracellularly and extracellularly to safe products (CO 2 and H 2 O) by soil and water microflora (Sudesh et al 2000;Jendrossek 2001). Although this is a relatively new application of PHAs, they have been successfully used to embed herbicides (Prudnikova et al 2013;Boyandin et al 2016;Volova et al 2016a,b), fungicides (Savenkova et al 2002;Volova et al 2016c,d), and nitrogen fertilizers (Volova et al 2016e).…”
Section: Discussionmentioning
confidence: 99%
“…Hydroxybutyrate-co-hydroxyvalerate copolymers were used as carriers for the herbicides atrazine and ametryn [12][13][14]. A series of studies described P(3HB) microparticles, granules, films, and pellets loaded with the herbicide metribuzin and the fungicide tebuconazole; release kinetics of the active ingredients and degradation of the polymer matrix were investigated in soil microecosystems [15][16][17]. The efficacy of the formulations was evaluated in laboratory wheat ecosystems contaminated with weeds and infected with fusarium pathogens [18][19].…”
Section: Introductionmentioning
confidence: 99%